2011
DOI: 10.1016/j.bcmd.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Uroporphyria in the Cyp1a2−/− mouse

Abstract: Cytochrome P4501A2 (Cyp1a2) is important in the development of uroporphyria in mice, a model of porphyria cutanea tarda in humans. Heretofore, mice homozygous for the Cyp1a2−/− mutation do not develop uroporphyria with treatment regimens that result in uroporphyria in wild-type mice. Here we report uroporphyria development in Cyp1a2−/− mice additionally null for both alleles of the hemochromatosis (Hfe) gene and heterozygous for deletion of the uroporphyrinogen decarboxylase (Urod) gene (genotype: Cyp1a2−/−; H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Animal models representing the hereditary porphyrias have been generated for all porphyria subtypes except for HCP and aminolevulinic acid dehydratase deficiency porphyria (ADP) ( Richard et al, 2008 ; Homedan et al, 2015 ; Medlock et al, 2002 ; Phillips et al, 2011 ). These animal models have been vital for the understanding of mitochondrial biosynthesis pathways and the development of novel gene replacement therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models representing the hereditary porphyrias have been generated for all porphyria subtypes except for HCP and aminolevulinic acid dehydratase deficiency porphyria (ADP) ( Richard et al, 2008 ; Homedan et al, 2015 ; Medlock et al, 2002 ; Phillips et al, 2011 ). These animal models have been vital for the understanding of mitochondrial biosynthesis pathways and the development of novel gene replacement therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Phillips et al . demonstrated that the development of uroporphyria may be CYP1A2 independent but iron dependent. Thus, although the interaction between CYP1A2 and iron in uroporphyria is not fully understood, it is likely that they share a similar pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the direct link between CYP1A2 and iron metabolism in mice is not fully elucidated. Recent work suggests that uroporphyria may be CYP1A2 independent . Although there is a great homology in CYP1A2 gene between human and mouse , in human, there is wide genotype variability and no definite genotype–phenotype correlation .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ferrous iron was found to generate uroporphomethene independently of CyP450-enzymes. 75,78 This mechanism has only been confirmed in homogenates of human liver biopsies, where an inhibitor of UROD has been identified in patients with PCT. Patients with PCT usually carry polymorphic variants of CyP450 genes, leading to higher enzyme activities, whereas patients with familial PCT express a polymorphic variant of glycerol phosphate Oacyltransferase that is associated with iron accumulation in HFE-associated hemochromatosis.…”
Section: Pathophysiologymentioning
confidence: 99%